Neuromuscular recovery of the biceps brachii muscle after resistance exercise - Oliveira, Anderson Souza [UNESP]; Gonçalves, Mauro [UNESP] (Taylor & Francis, 2008)
The aim of this study was to determine the time to restore the biceps brachii (BB) electromyographic (EMG) activity after the biceps curl (BC) exercise, at different intensities. Ten males performed initially maximal voluntary isometric contractions (MVC) of the elbow flexors, followed by one isometric submaximal contraction at 50% MVC (reference contraction). After this, four bouts of the BC at 25%, 30%, 35%, and 40% 1 RM during 1 minute (randomly assigned, with 10 minutes rest between them) were performed. During the rest intervals at preestablished moments (15 seconds, 1, 3, 5, and 10 min), isometric 50% MVC were performed. The EMG variables (root mean square [RMS], zero crossings [ZC], median frequency, [MF] and peak power [PP]) at rest were compared with reference values. Immediately after the exercise, RMS and PP increased, while ZC and MF decreased, indicating fatigue. After 1 minute most of the variables were similar to the reference. Different load levels did not affect the EMG recovery. In conclusion, the EMG variables recovered after 1 minute rest, indicating the optimal muscular condition for subsequent bouts. Copyright © Taylor & Francis Group, LLC.
Keywords: Amplitude; Biceps brachii; Electromyography; Frequency; Recovery; adult; biceps brachii muscle; elbow flexion; electromyogram; exercise; human; human experiment; male; muscle fatigue; muscle isometric contraction; muscle strength; neuromuscular function; normal human; reference value; Arm; Humans; Isometric Contraction; Male; Muscle Fatigue; Muscle, Skeletal; Recovery of Function; Resistance Training; Rest; Time Factors; Young Adult